Identification of Factors Affecting Modal Shift in Lahore : Factors Affecting Modal Shift in Lahore - Majeed, Sulaiman; Batool, Zahara (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The popularity of Metro Bus System (MBS) on the whole is increasing in different cities of developing countries that are looking for cost effective sustainable mass transit solutions. One such example is Lahore, which is under grave influence of poor urban public transportation system. To improve this, MBS was introduced on one of its busiest corridors from Shahdara to Gajjumatta in 2013. The idea proved to be a great success since it started achieving its objectives i.e. to shift the commuters from their self owned vehicles or para-transit system to a mass transit system. It is very efficient, comfortable and cost effective public transport service. This study aimed at studying the key indicators that influence possible modal shift that can be achieved as a result of extension of MBS from Shahdara to Kala Shah Kaku (KSK). For the rationale to fulfill this research, a road user perception interview survey wasconducted in the study area. A Model is developed using binary logistic regression for MBS and Qingqi. The possible modal shift from Qingqi is also studied. It is estimated that 89% of the commuters are willing to shift from Qingqi to the proposed MBS. These potential commuters primarily belonged to lower-middle income group and their mode choice is predominantly influenced by travel time, travel distance and cost. Travel time was found to be the most significant variable. It is suggested that providing mass transit system with low fares and minimum headway may be a great success on this corridor.